YouTube as a source of medical information about epidural analgesia for labor pain. (February 2021) - D'Souza, R.S.; D'Souza, S.; Sharpe, E.E.
Highlights: We appraised accuracy and quality of YouTube videos about epidural labor analgesia. More than 20% of the videos contained non-factual information. Hospitals and medical professionals posted the highest video quality. Videos from reputable sources such as professional societies are underrepresented. Accurate medical information dissemination is needed on social media platforms. Abstract: Background: Large gaps remain in our understanding of the role of social media platforms in the dissemination of medical information. This cross-sectional study quantitatively assessed the accuracy and quality of information on YouTube regarding epidural labor analgesia. Methods: YouTube was searched on May 23, 2020 using keywords 'epidural, ' 'epidural for labor, ' 'epidural for pregnancy, ' 'epidural experience, ' and 'epidural risks, ' and the top 50 viewed videos from each search were screened. Primary outcomes included the proportion of videos containing non-factual information, and video quality analyzed using the modified DISCERN (mDISCERN) score. Results: Thirteen of 60 (21.7%) videos included non-factual information about epidural analgesia; these videos were viewed more than 16.5 million times (60% of total viewership of the videos analyzed). Mean (standard deviation) mDISCERN score for all included videos was 1.9 (1.3), which is below the threshold for high video-quality. Videos from medical sources (hospitals, medical practices, physicians, other medical professionals) had a higher mDISCERN score compared with videos by non-medical sources ( P <0.001). Educational videos from professional societies of obstetrics or obstetric anesthesiology were not captured. Conclusion: YouTube is an accessible platform for medical information on epidural labor analgesia, although a significant proportion of videos studied contained non-factual information and presented low video quality. Increased efforts by reputable sources including hospitals, physicians, other medical professionals, and professional societies, to disseminate accurate information, are warranted.